Estudo de deformação vertical de pavimento para o dimensionamento de recapeamentos - Queiroz, César Augusto Vieira de (1972)
A new feature concerning design of overlays for flexible pavements is presented. The development is based on the expression of surface deflection according to the theory of elasticity for a two-layered system, and with due consideration of empirical correlation between traffic characteristics and allowable deflection. Starting from Huang's solution for the deflection in a two-layered system at an off-set from the loaded surface (single wheel), the Author obtains the deflection at center of twin wheels and develops an automatic program in FORTRAN computer language for it. The effective modulus of elasticity of the existing pavement and subgrade soil altogether is admitedly determited from deflection measurements with the Benkelman beam. It is described a field work performed in order to determine the characteristics of the 9000 lbs twin wheels - imprint area, tyre pressure, etc - which is the usual load for Benkelman beam determinations. The theoretical development gives us means to determine the overlay thickness provided its modulus of elasticity is known. A graph for this sort of calculations is shown. A comparison is made with existing methods of flexible pavement overlay design.